The persistence of distance: A macro-level perspective on European cross-border real estate development flows. Issue 2 (3rd August 2015) - Sherrin, Catherine; McAllister, Patrick; Nanda, Anupam
Abstract : Purpose: – This paper aims to investigate the scale and drivers of cross-border real estate development in Western Europe and Central and Eastern Europe. Design/methodology/approach: – Placing cross-border real estate development within the framework of foreign direct investment (FDI), conceptual complexities in characterizing the notional real estate developer are emphasized. Drawing upon a transaction database, this paper proxies cross-border real estate development flows with asset sales by developers. Findings: – Much higher levels of market penetration by international real estate developers are found in the less mature markets of Central and Eastern Europe. Analysis suggests a complex range of determinants with physical distance remaining a consistent barrier to cross-border development flows. Originality/value: – This analysis adds significant value in terms of understanding cross-border real estate development flows. In this study, a detailed examination of the issues based on a rigorous empirical analysis through gravity modelling is offered. The gravity framework is one of the most confirmed empirical regularities in international economics and commonly applied to trade, FDI, migration, foreign portfolio investment inter alia . This paper assesses the extent to which it provides useful insights into the pattern of cross-border real estate development flows.